Implementation Of The Regulation Of The Minister Of Religious Affairs Number 31 Of 2020 On Islamic Boarding School Education In Character Development At Darussalam Islamic Boarding School, Bengkulu City - Sari, Mala; Yusuarsono, Yusuarsono; Maryaningsih, Maryaningsih (Utami Publisher, 2025)
The purpose of this research is to describe the implementation of the Regulation of the Minister of Religious Affairs Number 31 of 2020 on Islamic boarding school education in character development at Darussalam Islamic Boarding School, Bengkulu City. This research used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Informants were selected using purposive sampling, consisting of 4 individuals. The analysis is based on Van Meter and Van Horn’s implementation theory which includes six indicators: policy standards and objectives, resources, inter-organizational communication, characteristics of implementers, disposition, and economic, social, and political conditions. The findings indicate that policy standards and goals align with the Standard Operating Procedures and target outcomes. Resources including facilities and infrastructure are adequate. Communication among teachers is well-coordinated. Implementers demonstrate competence and discipline in carrying out character development. There is a willingness among implementers to run the program. Economically, the environment supports the character development process. However, the lack of political support and the location of the school on a major road are social obstacles to character development.